2019
DOI: 10.1001/jamafacial.2018.0308
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Anatomical Outcomes of Facial Nerve Injury With Application of Polyethylene Glycol in a Rat Model

Abstract: IMPORTANCE Functional and anatomical outcomes after surgical repair of facial nerve injury may be improved with the addition of polyethylene glycol (PEG) to direct suture neurorrhaphy. The application of PEG has shown promise in treating spinal nerve injuries, but its efficacy has not been evaluated in treatment of cranial nerve injuries. OBJECTIVE To determine whether PEG in addition to neurorrhaphy can improve functional outcomes and synkinesis after facial nerve injury. DESIGN, SETTING, AND SUBJECTS In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…Whether the labeled axons ever reinnervated the correct or incorrect muscle is never assessed. Brown et al (2018) conclude that "polyethylene glycol fusion has shown efficacy in the surgical repair of spinal nerve injuries, but this finding was not replicated in facial nerve injury repair." However, Brown et al (2018) almost-certainly did not induce PEG-fusion repair because of technical issues including use of: 1) 500mM PEG solution rather than a 50% w/w (500millimolal) solution, 2) isotonic rather than hypotonic conditioning solutions, and/or 3) an unstated solution of MB.…”
Section: Proper Interpretation Of Peg-fusion Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the labeled axons ever reinnervated the correct or incorrect muscle is never assessed. Brown et al (2018) conclude that "polyethylene glycol fusion has shown efficacy in the surgical repair of spinal nerve injuries, but this finding was not replicated in facial nerve injury repair." However, Brown et al (2018) almost-certainly did not induce PEG-fusion repair because of technical issues including use of: 1) 500mM PEG solution rather than a 50% w/w (500millimolal) solution, 2) isotonic rather than hypotonic conditioning solutions, and/or 3) an unstated solution of MB.…”
Section: Proper Interpretation Of Peg-fusion Protocolsmentioning
confidence: 99%
“…Brown et al (2018) conclude that "polyethylene glycol fusion has shown efficacy in the surgical repair of spinal nerve injuries, but this finding was not replicated in facial nerve injury repair." However, Brown et al (2018) almost-certainly did not induce PEG-fusion repair because of technical issues including use of: 1) 500mM PEG solution rather than a 50% w/w (500millimolal) solution, 2) isotonic rather than hypotonic conditioning solutions, and/or 3) an unstated solution of MB. Furthermore, they performed no intraoperative assays to demonstrate successful PEG-fusion, i.e., to confirm that they successfully PEG-fused proximal and distal ends of some axons at the lesion site.…”
Section: Proper Interpretation Of Peg-fusion Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…At variance with the above-mentioned studies, Robinson et al reported that PEG fusion disrupted the beneficial trophic influence of muscle on motor neuron reinnervation accuracy in rats [121]. Moreover, Brown et al reported that PEG did not exert beneficial effects in the regeneration of facial nerve injury in rats [122].…”
Section: Pcl Polymermentioning
confidence: 99%
“…Polyethylene glycol (PEG), a linear polymer derived from ethylene oxide, finds a broad range of application in both biomedical and industrial sections [19][20][21][22]. It is regarded as one of the Egypt.J.Chem.…”
Section: Introductionmentioning
confidence: 99%